The impact of perineural invasion on prognosis in esophageal cancer patients after surgery: a systematic review and meta-analysis - Xiong, Jicheng; Liang, Shuoming; Lu, Simiao; Chen, Hainan; Wang, Ziwei; Meng, Hao; Zhu, Yi; Han, Yongtao; Leng, Xuefeng (Frontiers in Oncology, 2025)
ObjectiveThis study aims to update the prognostic value of perineural invasion(PNI) in various subgroups of esophageal cancer patients.MethodsWe searched databases including PubMed, Scopus, Wiley, Web of Science, and Embase for full-text articles published in English on esophageal cancer related to PNI. The search was conducted up to January 1, 2024. We summarized the hazard ratios (HR) and 95% confidence intervals (CI) for overall survival (OS), disease-free survival (DFS), as well as recurrence and metastasis, to assess the prognostic value of PNI in patients with esophageal cancer.ResultsA total of 38 eligible studies were ultimately included. Thirty-two studies, encompassing a total of 7157 patients, reported the correlation between PNI and OS. The results indicated that PNI is significantly associated with poor OS in esophageal cancer patients (HR = 1.54, 95% CI: 1.41-1.68, P < 0.00001). Eleven studies, including a total of 2224 patients, reported the correlation between PNI and DFS. These studies found that PNI is significantly associated with poor DFS (HR = 1.43, 95% CI: 1.25-1.62, P < 0.00001). Three studies, including a total of 1125 patients, reported no correlation between PNI and recurrence (HR = 1.17, 95% CI: 0.62-2.18, P = 0.63). Two studies, including a total of 556 patients, reported a correlation between PNI and distant metastasis (HR = 2.19, 95% CI: 1.02-4.73, P = 0.04). Further subgroup analysis revealed that PNI is an independent prognostic factor for esophageal squamous cell carcinoma (ESCC) (OS: HR=1.62, 95%CI: 1.35-1.94, P<0.00001; DFS: HR=1.28, 95%CI: 1.03-1.59, P=0.03); however, in esophageal adenocarcinoma, PNI is not associated with OS or DFS (OS: HR=1.23, 95%CI: 1.00-1.53, P=0.05; DFS: HR=1.65, 95%CI: 0.95-2.87, P=0.08). PNI positivity is associated with unfavorable outcomes, irrespective of neoadjuvant therapy receipt. In the non-Asian subgroup, PNI is not statistically significant for poor DFS prognosis.ConclusionPNI is a histological marker of aggressive disease and can serve as an independent prognostic factor for patients with esophageal cancer. PNI positivity can predict poor outcomes in ESCC, but its role as a prognostic indicator for adenocarcinoma requires further investigation.